ANALISIS PENDAPATAN PEDAGANG PUSAT PERBELANJAAN DEPOK JAYA SEBELUM DAN SESUDAH ADANYA SISTEM SATU ARAH DI KOTA DEPOK JAWA BARAT - Vira Fitriani; Oot Hotimah; Aris Munandar (Jurnal Ekonomi-Qu, 2022)
The goal of this study is to see how income and location differed before and afterimplemented a one-way system. The population in this study consisted of all traders in the Depok Jaya Shopping Center, with 61 samples based on purposive sampling criteria. A descriptive quantitative method was applied in this research. The difference income before and after the oneway system was implemented at the Depok Jaya Shopping Center was determined using descriptive percentages and a paired T-test in this study. The paired t-test findings reveal that for gross income, the t-count value (23,463) is more than the t table (2,00030) with a decrease in gross income of Rp. 1,155,737.705 for net income, the t-count value (15,957) is greater than the t table (2,00030) with a decrease in net income of Rp. 346,721.331, indicating that H0 is rejected and H1 is accepted, indicating a difference. the average income in Depok Jaya Shopping Center before and after the oneway system was implemented.